A statistical analysis of the correlates of compliance and defiance of seatbelt use. (February 2021) - Farooq, Muhammad Umer; Ahmed, Anwaar; Saeed, Tariq Usman
Highlights: A questionnaire survey was conducted. Policy implications of the empirical analysis are duly discussed. Strict enforcement of seatbelt laws needed. Abstract: With the intent to frame policy recommendations for enhancing the state of road safety, this study employed a binary logit regression approach to examine the factors associated with the compliance/defiance of seatbelt use among drivers of different vehicle types in Islamabad. To this end, a questionnaire survey was conducted to collect data on the respondents' seatbelt use, demographic characteristics, driving behavior, past penalization history, and perceived effectiveness of enforcement of seatbelt laws. The study results revealed that there is a lower likelihood of wearing seatbelt among male drivers, taxi drivers, drivers with a low level of education, drivers with no crash or injury history, drivers that violate speed limits and are never penalized on seatbelt violation, and drivers with no seatbelt reminder installed in their vehicles. Respondents who believed that there is low effectiveness of the enforcement of seatbelt laws had the highest impact on seatbelt use whereas, the presence of seatbelt reminders in the vehicle had the least impact on seatbelt use. The findings of this study suggest the need for awareness campaigns for taxi drivers with the intent to educate them about the potential benefits of using a seatbelt in the case of a crash event; improved awareness and strict vigilance of male drivers; strict enforcement of posted speed limits and seatbelt laws; legislation for the mandatory installation of a seatbelt in all the new vehicles, and organizing mass outreach campaigns to improve the overall safety environment. Most importantly and widely applicable to the developing world, this study necessitates a depiction of strong resolve on the part of government agencies regarding the strict enforcement of seatbelt laws. Given a substantial difference in the social, cultural, and legislative outfit of the developed and developing worlds, factors influencing the compliance/defiance of seatbelt use among drivers differ significantly. It is, therefore, important to explore the local contributory factors as the results are not necessarily transferable across the regions.